(untitled) (World Economics and Finance Bulletin, 2026)
This article analyzes the priority areas and practical aspects of developing the internal audit system in non-state higher education institutions in Asian countries. The study highlights the role of the internal audit service in the management system of higher education institutions, its importance in risk management, improving the effectiveness of internal control, and improving corporate governance. Based on the experience of India, Singapore, Malaysia, Japan, and other countries in the Asian region, the institutional mechanisms for organizing internal audit in non-state higher education institutions, a riskbased audit approach, information technology audit, and practices for ensuring transparency and accountability were studied. The study revealed that the main areas of development of internal audit activities, including academic and administrative process audits, digital risk control, strengthening integrity and compliance systems, and integrating audit activities with corporate governance institutions are important factors. The results of the study serve to improve the internal audit system in non-state higher education institutions, strengthen management transparency and financial discipline, and support strategic development.